Implementasi Pembelajaran Berbasis Audio Visual Dalam Meningkatkan Konsentrasi Belajar Anak Usia 5-6 Tahun Di Ra Nurul Islam - Firdausih, Intan; Travelancya DP, Terza; Ali, Mahfudz (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2025)
This study explores the implementation of audiovisual-based learning at RA Nurul Islam to improve the concentration of learning in children aged 5-6 years. Early age is an important period in the development of children's education, where experience and environmental stimulation play a very important role. This study identified children's difficulties in concentrating and understanding learning materials due to less interactive teaching methods. By implementing audiovisual media, such as videos and animations, children can more easily understand information. The results showed that the use of audio and visual elements was effective in increasing interest and concentration in learning, as well as encouraging active participation in children. RA Nurul Islam is committed to creating an interactive learning environment with group assessments. These findings indicate that audiovisual-based learning not only improves concentration, but also provides a more meaningful and enjoyable educational experience for children.